2016
DOI: 10.1097/ijg.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Change in Intraocular Pressure in the Fellow Eye After Glaucoma Surgery in 1 Eye

Abstract: Glaucoma surgery in eye is associated with a rise in IOP of the fellow eye, regardless of whether the fellow eye is normal or glaucomatous, or had been previously treated with acetazolamide. Fellow eyes of all patients scheduled for glaucoma surgery require careful monitoring of the IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…In our study, we found that the mean IOP for the contralateral control eyes significantly increased when compared to its mean baseline IOP value in the Group 1 primates, although the mean IOPs in the OHT period between months 2-7 did not exceed 20 mmHg (Table 1). This finding seems to corroborate those of previous studies [33][34][35][36] . A consensual IOP rise has been frequently reported in both experimental and clinical glaucoma studies [33][34][35]37 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, we found that the mean IOP for the contralateral control eyes significantly increased when compared to its mean baseline IOP value in the Group 1 primates, although the mean IOPs in the OHT period between months 2-7 did not exceed 20 mmHg (Table 1). This finding seems to corroborate those of previous studies [33][34][35][36] . A consensual IOP rise has been frequently reported in both experimental and clinical glaucoma studies [33][34][35]37 .…”
Section: Discussionsupporting
confidence: 93%
“…This finding seems to corroborate those of previous studies [33][34][35][36] . A consensual IOP rise has been frequently reported in both experimental and clinical glaucoma studies [33][34][35]37 . Although the exact mechanism for this consensual IOP effect has not been elucidated, postulated mechanisms include: glaucoma drug effects 36 ; activation of sympathetic neural signals in the anterior segment that might increase the aqueous outflow 34 ; anterior chamber cannulation that activates microglia 37 ; and prostaglandin release that might exert a minor effect on the trabecular meshwork and thus cause a minor IOP elevation 35,37 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… 16 20 However, choroidal expansion mechanism seems to be more effective in angle closure eyes than in open-angle eyes or healthy eyes and this was quantified with optical coherence tomography studies. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%